Transformasi Kurikulum di Indonesia : Implementatif terhadap KTSP 2006, K-13 dan Kurikulum Merdeka - Herlina Jasa Putri Harahap; Puput Diva Taqdira Siregar; Demak Angel Paustina Br Sitanggang; Enjelica Damayanti Purba; Lamtiur Riris Tua Silaban; Anjany Pandiangan (Lembaga Pengembangan Kinerja Dosen, 2025)
Curriculum transformation in Indonesia reflects the government's efforts to adapt the education system to the times. This article examines the implementation of the 2006 KTSP curriculum, the 2013 Curriculum, and the Merdeka Curriculum. The study was conducted through a descriptive qualitative approach with a literature study method from various relevant sources. The 2006 KTSP gives schools broad authority to develop a curriculum according to local needs. The 2013 Curriculum is here to strengthen the scientific approach and character education. The Merdeka Curriculum is a response to the challenges of learning in the digital era, offering flexibility, project-based learning, and a focus on developing the profile of Pancasila students. Although the Merdeka curriculum brings a spirit of renewal, the implementation of this Curriculum also faces obstacles in training, school readiness, and adaptation of learning culture. This study concludes that curriculum changes in Indonesia show an increasingly progressive direction, but the success of its implementation is highly dependent on the overall support and collaboration of all parties in the world of education.